Development of Culinary Tourism Through Cooking Classes and Processing of Local Souvenirs in Pabean Village - Taufikurrahman Taufikurrahman; Wahyuni Wahyuni; Lia Nirawati; Tegar Prayoga; Rifa Muhamad Rizki (Jurnal Pengabdian Masyarakat Al-Fatimah, 2024)
Pabean Village, located in Dringu Subdistrict, has significant potential for developing creative economy-based tourism. However, limited human resources and expertise in the tourism sector remain major obstacles to fully realizing this potential. In 2023, the UPN Mengabdi team conducted a community service program in this village, focusing on assisting in the development of educational tourism packages. The program aimed to optimize the potential of local MSMEs, crafts, culture, home industries, livestock, plantations, and agriculture in the area. Currently, the residents of Pabean Village primarily sell raw shallots, with some processing them into fried shallots. However, there have been no initiatives to transform shallots into ready-to-eat food products with higher market value. Local ingredients hold significant potential for being creatively developed into a variety of new culinary products. Based on this background, the UPN “Veteran” Jawa Timur community service team designed a training program that includes: 1) Training on creating Pabean Village’s signature souvenirs, such as various ready-to-serve sambal products, and 2) Training on developing cooking class-based tourism packages, targeting families, school children, and women’s groups as the primary tourist segments